2021
DOI: 10.3390/rs13204063
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Vegetation Greenness and Its Response to Climate Change in Xinjiang over the Past Two Decades

Abstract: Climate change has proven to have a profound impact on the growth of vegetation from various points of view. Understanding how vegetation changes and its response to climatic shift is of vital importance for describing their mutual relationships and projecting future land–climate interactions. Arid areas are considered to be regions that respond most strongly to climate change. Xinjiang, as a typical dryland in China, has received great attention lately for its unique ecological environment. However, comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…For example, after the collapse of the Soviet Union, Kazakhstan promoted the reclamation and development of agricultural land, and after 2000 there were spatial changes in croplands, but the total area was relatively stable and remained almost unchanged [58,59]. The Ili Valley region of China, meanwhile, has experienced extensive agricultural development over the past two decades, and cropland growth has been largely stable [41,60]. This situation may also have implications for simulations based on longer interval land use data under a natural scenario.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after the collapse of the Soviet Union, Kazakhstan promoted the reclamation and development of agricultural land, and after 2000 there were spatial changes in croplands, but the total area was relatively stable and remained almost unchanged [58,59]. The Ili Valley region of China, meanwhile, has experienced extensive agricultural development over the past two decades, and cropland growth has been largely stable [41,60]. This situation may also have implications for simulations based on longer interval land use data under a natural scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Dust emission can directly influence the dust aerosol concentration in the atmosphere [7,71,72], which is determined by the complex interactions among vegetation, climate, soil properties, and land use [13,44]. Previous studies have reported that the vegetation greenness increased in Xinjiang over the past 20 years [73][74][75][76][77], but some studies found that the vegetation degraded in northern Xinjiang, and the vegetation cover decreased in spring [75,78,79], which may be partly responsible for the increase in dust concentrations due to the increased spring dust emissions in this region [44].…”
Section: Discussionmentioning
confidence: 99%
“…The Xinjiang oasis region's arable land area is expanding and has the greatest greening rate of any vegetation type in the region (J. Xue et al, 2021), which is primarily driven by an increase in irrigation inputs (Cai et al, 2021). Irrigation can stabilize agricultural yields by mitigating the detrimental impacts of excess heat and low precipitation on crop growth (Troy et al, 2015).…”
Section: Effects Of Agricultural Irrigation On Structural Overshootmentioning
confidence: 99%